Changes in Some Health and Lifestyle Behaviours Are Significantly Associated with Changes in Gambling Behaviours: Findings from a Longitudinal New Zealand Population Study - E. Bellringer, Maria; Janicot, Stéphane; Ikeda, Takayoshi (Elsevier BV, 2023)
Although a large number of studies have investigated associations between risky gambling behaviours and health, lifestyle and social factors, research has not focused on changes in these factors and associations with changes in gambling risk level. This study utilised existing data from the four waves of the longitudinal New Zealand National Gambling Study to examine associations between changes in substance use, mental and physical health, and quality of life and deprivation with changes in gambling risk level over time. A Markov chain transition model was used to perform these analyses using data from participants who had completed all four waves (11,080 data transitions). Although changes in various covariates were associated with changes in all gambling risk levels, the highest number of significant factors was for transitioning into risky gambling from non-problematic gambling, including development, or continuation, of several negative health and lifestyle factors that may possibly be alleviated by transitioning out of risky gambling. These findings highlight the importance of screening for gambling behaviours when assisting people with substance use, health issues, or social situations or conditions in order to provide appropriate and effective social, health and treatment supports for people whose gambling behaviour increases over time.
Keywords: 1117 Public Health and Health Services; 1701 Psychology; Substance Abuse; 4206 Public health; 5202 Biological psychology; 5203 Clinical and health psychology